Ship-shaped offshore installations : design, building, and operation - Paik, Jeom Kee (Cambridge University Press, 2007)
Ship-shaped offshore units are some of the more economical systems for the development of offshore oil and gas, and are often preferred in marginal fields. These systems are especially attractive to develop oil and gas fields in deep and ultra-deep water areas and remote locations away from existing pipeline infrastructures. Recently, the ship-shaped offshore units have been applied to near shore oil and gas terminals. It is an ideal text and reference on the technologies for design, building and operation of ship-shaped offshore units, within inevitable space (and time) requirements. The book includes a range of topics, from the initial contracting strategy to decommissioning and the removal of the units concerned. Coverage includes both fundamental theory and principles of the individual technologies. This book will be useful to students who will be approaching the subject for the first time as well as designers working on the engineering for ship-shaped offshore installations.
Keywords: Drilling platforms.; Offshore structures -- Design and construction.; elektronické knihy; electronic books